Role of AS-OCT in Managing Corneal Disorders - Nidhi Gupta; Akhil Varshney; Muralidhar Ramappa; Sayan Basu; Vito Romano; Manisha Acharya; Abha Gaur; Neha Kapur; Aastha Singh; Gaurav Shah; Isha Chaudhary; Nikunj Patel; et al. (Diagnostics, 2022)
Optical coherence tomography (OCT) is analogous to ultrasound biometry in the cross sectional imaging of ocular tissues. Development of current devices with deeper penetration and higher resolution has made it popular tool in clinics for visualization of anterior segment structures. In this review, the authors discussed the application of AS-OCT for diagnosis and management of various corneal and ocular surface disorders. Further, recent developments in the application of the device for pediatric corneal disorders and extending the application of OCT angiography for anterior segment are introduced.